99.8k views
0 votes
​Solve for x.

−2(x+13)+9x=4 ​



​Enter your answer as a fraction in simplest form in the box.

2 Answers

1 vote

Answer: 4 2/7 or if they want improper 30/7

Explanation:

-2(x + 13) + 9x = 4

Distribute the -2 to the parentheses

-2x - 26 + 9x = 4

Combine like terms

7x - 26 = 4

Add 26 to both sides to get x by itself

7x = 30

Divide by 7 to get x by itself.

x = 30/7

Mixed = 4 2/7 normal = 30/7

User Fabian Hertwig
by
5.2k points
4 votes

Answer:

- 9/7

Explanation:

7x + 13 = 4

- 13 = -13

7x= -9

x = -9/7

User Allie Hoch Janoch
by
4.8k points